Evaluasi Kinerja Pelayanan Gerbang Tol Marelan Berdasarkan Model Antrian First In First Out (FIFO) - Liza Evianti Tanjung; Salsa Al-Kahfi; Muhammad Husin Gultom (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
The rapid growth of vehicle numbers in urban areas has increased the need for efficient transportation systems. Toll roads are one solution to enhance mobility and reduce congestion on major road networks. However, congestion frequently occurs at toll gate areas due to an imbalance between vehicle arrival rates and toll booth service rates. This study aims to analyze the capacity and service performance of the Marelan Toll Gate in Medan City using a queuing theory approach. The research data were obtained through field surveys to determine vehicle arrival rates and service times during peak hours. The analysis was conducted using a queuing model with a FIFO (First In First Out) service discipline. The results indicate that the service capacity of each toll booth is approximately 214 vehicles per hour. During peak conditions, the vehicle arrival rate approaches the service capacity, resulting in the formation of vehicle queues. Therefore, improving service system efficiency is necessary through optimizing the number of toll booths and implementing electronic toll transaction systems to enhance the overall performance of the toll gate.